Oblicza tożsamości brytyjskiej w poglądach wybranych historyków brytyjskich drugiej połowy XX wieku - Nowakowska-Dryk, Anna (Acta Universitatis Lodziensis. Folia Historica, 2003)
The article Images of the British Identity in the Views of the Chosen British Historians of the Middle of the Twentieth Century is a condensed view of a Polish historian on the problem of various attitudes towards the British National Identity phenomenon in the British historiography of the middle of the twentieth century. It shows opinions of the researchers belonging to different schools of history and options present on the British Island during the period. It is based on the views of chosen representatives of the modern British historiography. A conspicuous part of the article is devoted to the views of Scottish historians as the problem rouses a vivid interest among them. The problem of the British Islands common identity is not widely known in Poland but it evokes numerous areas of the research, both by its local implications and general conception. The article is to familiarize Polish readers with the changing paths of understanding the ideas of nation, patriotism, Scoltishness or Britishness itself and the circumstances influencing their interpretation and present sense. None of them makes a homogeneous and immutable term. The different images of the British identity phenomenon with a huge variety of its components is the integral part of the British historiography of the middle of the twentieth century and the subject of numerous research approaches causing various conclusions.